Sickle Cell Trait Causing Splanchnic Venous Thrombosis - Priyanka Saxena; Pratibha Dhiman; Chhagan Bihari; Archana Rastogi (Case Reports in Hepatology)
Sickle cell trait is considered as a benign condition as these individuals carry only one defective gene and typically have their life span similar to the normal population without any health problems related to sickle cell. Only under extreme conditions, red cells become sickled and can cause clinical complications including hematuria and splenic infarction. Although twofold increased risk of venous thrombosis has been described in African Americans, there is no data available from Indian population. We here report a case of sickle cell trait from India whose index presentation was thrombosis of unusual vascular territory.